Context‐dependent vertical transmission shapes strong endosymbiont community structure in the pea aphid, Acyrthosiphon pisum. Issue 8 (27th December 2017) - Rock, Danielle I.; Smith, Andrew H.; Joffe, Jonah; Albertus, Amie; Wong, Narayan; O'Connor, Michael; Oliver, Kerry M.; Russell, Jacob A.
Abstract: Animal‐associated microbiomes are often comprised of structured, multispecies communities, with particular microbes showing trends of co‐occurrence or exclusion. Such structure suggests variable community stability, or variable costs and benefits—possibilities with implications for symbiont‐driven host adaptation. In this study, we performed systematic screening for maternally transmitted, facultative endosymbionts of the pea aphid, Acyrthosiphon pisum . Sampling across six locales, with up to 5 years of collection in each, netted significant and consistent trends of community structure. Co‐infections between Serratia symbiotica and Rickettsiella viridis were more common than expected, while Rickettsia and X‐type symbionts colonized aphids with Hamiltonella defensa more often than expected. Spiroplasma co‐infected with other endosymbionts quite rarely, showing tendencies to colonize as a single species monoculture. Field estimates of maternal transmission rates help to explain our findings: while Serratia and Rickettsiella improved each other's transmission, Spiroplasma reduced transmission rates of co‐infecting endosymbionts. In summary, our findings show that North American pea aphids harbour recurring combinations of facultative endosymbionts. Common symbiont partners play distinct roles in pea aphid biology, suggesting the creation of "generalist" aphids receiving symbiont‐based defence against multiple ecological stressors. Multimodal selection, at the host level, may thus partially explain our results. But more conclusively, our findings show that within‐host microbe interactions, and their resulting impacts on transmission rates, are an important determinant of community structure. Widespread distributions of heritable symbionts across plants and invertebrates hint at the far‐reaching implications for these findings, and our work further shows the benefits of symbiosis research within a natural context.